The Role Of The School Environment In Shaping Children's Character - Lilawati, Agustien (STAI Miftahul Ula Nganjuk, 2024)
Early childhood is considered a golden age where children possess exceptional potential and talents if optimally stimulated. However, current educational practices often fall short in achieving educational goals, particularly in character building. Issues such as bullying in schools indicate that children may develop poor behaviors due to unoptimized environmental roles. Recognizing the importance of instilling character education in children, a conducive environment significantly impacts their character formation. This study aims to understand the role of the school environment in shaping the character of Group B children at RA Dwi Savitri Surabaya. The study focuses on five character traits as per the Ministry of Education and Culture's guidelines: Rationality, Nationalism, Independence, Cooperation, and Integrity. Respondents include teachers and children at RA Dwi Savitri. Using a descriptive qualitative approach and case study design, data were analyzed through interviews and observations. Findings show that character development at RA Dwi Savitri is consistently practiced daily. Religious character is fostered through routines like reciting short surahs, Asmaul Husna, performing Dhuha prayers, and daily prayers from 08:00 to 09:00. Nationalism is developed by reciting the Pancasila, singing the national anthem, and engaging in Independence Day activities. Independence is encouraged through self-feeding and independent learning. Cooperation is taught through group activities, sharing, and community events. Integrity is instilled through an honesty canteen, saving pocket money, completing school tasks, and punctuality.